Kekerasan Berbasis Gender terhadap Perempuan Penyandang Disabilitas dalam Dunia Kerja: Tinjauan Kebijakan Publik di Indonesia - Novianty, Silvy; Aulia, Aisyah; Ananta, Assyfa Futri; Pangestoeti, Wahjoe (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Women with disabilities are a group that is highly vulnerable to gender-based violence, particularly in the workplace. Such violence does not only take the form of direct physical abuse, but also manifests through discrimination, stigma, and the systemic neglect of rights. This study aims to analyze forms of gender-based violence experienced by women with disabilities in the world of work and to examine the role of public policy in providing protection. This research employs a qualitative approach using a literature review method by analyzing ten academic journals and five national media reports relevant to the topic. The findings indicate that women with disabilities experience multiple forms of discrimination resulting from the intersection of gender and disability, which limits their access to decent employment and effective legal protection. Although various policies addressing disability rights and the prevention of gender-based violence have been established in Indonesia, their implementation remains insufficiently responsive to the specific needs of women with disabilities. Therefore, strengthening public policies that integrate gender and disability perspectives is essential to creating an inclusive, equitable, and violence-free working environment.